SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The impact of disease and species differences on the intestinal CLCA4 gene expression - K. Teske; N. A. Erickson; A. Huck; M. Dzamukova; M. Fulde; T. Heinbokel; D. Horst; N. Klymiuk; E. Pastille; A. Mekes-Adamczyk; M. Löhning; A. D. Gruber; et al. (Journal of Molecular Medicine, 2025)
The human chloride channel regulator, calcium-activated (CLCA) 4 is discussed as a driver of epithelial-to-mesenchymal transition as well as a biomarker for colorectal cancer (CRC) and ulcerative colitis. In contrast to humans, the Clca4 gene is duplicated in the mouse, a common model species to study gene functions. However, the relevance of the functional murine Clca4 variants in healthy and diseased intestine is largely unknown. Here, we characterized the spatiotemporal expression patterns of the murine Clca4a and Clca4b genes in the healthy intestinal tract as well as in dextran sulfate sodium (DSS)-induced colitis and colitis-associated colon cancer (CAC) mouse model using RT-qPCR and in situ-hybridization. Similarly, we analyzed expression of the human CLCA4 in healthy, inflamed and cancerous intestinal tracts at single cell level. Murine Clca4a and - 4b but not the human CLCA4 were detected in small intestine enterocytes of the respective species. Conversely, healthy colonocytes expressed the human CLCA4 and its murine ortholog Clca4a but not the murine Clca4b . Under inflammatory conditions, de novo expression of Clca4b was observed with both murine homologs abundantly expressed in enterocytes adjacent to ulcerations. Neoplastic colonocytes expressed none or only minimal amounts of the CLCA4 homologs both in humans and mice, whereas adjacent non-neoplastic colonocytes strongly up-regulated the human or both murine homologs, respectively. Our results suggest marked species- and homolog-specific differences in the expression patterns of the three CLCA4 homologs. Moreover, all three seem to play a role in reactive, non-neoplastic colonocytes adjacent to ulcerated and neoplastic lesions. Key messages Human CLCA4 and murine Clca4a , but not Clca4b , are expressed in healthy colonocytes. Inflammation leads to a de novo expression of the murine Clca4b in colonocytes. Human and murine CLCA4 homologs are absent from neoplastic enterocytes. Human and murine CLCA4 s are highly expressed in tumor-adjacent, reactive colonocytes.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Docosahexaenoic Acid (DHA) Supplementation Alters Phospholipid Species and Lipid Peroxidation Products in Adult Mouse Brain, Heart, and Plasma - Grace Y. Sun; Michael K. Appenteng; Runting Li; Taeseon Woo; Bo Yang; Chao Qin; Meixia Pan; Magdalena Cieślik; Jiankun Cui; Kevin L. Fritsche; Zezong Gu; Matthew Will; et al. (NeuroMolecular Medicine, 2021)

Anthropogenic disturbance homogenizes seagrass fish communities - Josephine C. Iacarella; Emily Adamczyk; Dan Bowen; Lia Chalifour; Aaron Eger; William Heath; Sibylla Helms; Margot Hessing‐Lewis; Brian P. V. Hunt; Andrew MacInnis; Mary I. O'Connor; Clifford L. K. Robinson; et al. (Global Change Biology, 2018)
Anthropogenic activities have led to the biotic homogenization of many ecological communities, yet in coastal systems this phenomenon remains understudied. In particular, activities that locally affect marine habitat‐forming foundation species may perturb habitat and promote species with generalist, opportunistic traits, in turn affecting spatial patterns of biodiversity. Here, we quantified fish diversity in seagrass communities across 89 sites spanning 6° latitude along the Pacific coast of Canada, to test the hypothesis that anthropogenic disturbances homogenize (i.e., lower beta‐diversity) assemblages within coastal ecosystems. We test for patterns of biotic homogenization at sites within different anthropogenic disturbance categories (low, medium, and high) at two spatial scales (within and across regions) using both abundance‐ and incidence‐based beta‐diversity metrics. Our models provide clear evidence that fish communities in high anthropogenic disturbance seagrass areas are homogenized relative to those in low disturbance areas. These results were consistent across within‐region comparisons using abundance‐ and incidence‐based measures of beta‐diversity, and in across‐region comparisons using incidence‐based measures. Physical and biotic characteristics of seagrass meadows also influenced fish beta‐diversity. Biotic habitat characteristics including seagrass biomass and shoot density were more differentiated among high disturbance sites, potentially indicative of a perturbed environment. Indicator species and trait analyses revealed fishes associated with low disturbance sites had characteristics including stenotopy, lower swimming ability, and egg guarding behavior. Our study is the first to show biotic homogenization of fishes across seagrass meadows within areas of relatively high human impact. These results support the importance of targeting conservation efforts in low anthropogenic disturbance areas across land‐ and seascapes, as well as managing anthropogenic impacts in high activity areas.